Energy harvesting from radial electro-hydraulic actuators in tracked armored vehicle suspensions under thermal constraints - An Huang; Yong Guo; Guosheng Wang; Qihui Ling; Yanfeng Peng; Weijie Zhang; Wensheng Peng (Energy Conversion and Management: X, 2025)
The electro-hydraulic energy-harvesting suspension system is crucial for enhancing the mobility and firing accuracy of tracked armored vehicles. However, its application is constrained by limited structural space and thermal loss issues. This paper designs an energy-harvesting suspension system based on radial electro-hydraulic actuators without a hydraulic rectifier bridge, addressing the challenge of integrating high-efficiency energy recovery with thermal management. A linear weighted fusion method is proposed to integrate efficiency and thermal loss power matrices, enabling a low-loss, high-efficiency vibration energy recovery strategy. Model predictive control (MPC) is employed to implement the strategy in tracked armored vehicle suspensions. Experimental results under sinusoidal excitation show that the system achieves a maximum energy recovery efficiency of 54.6 % (average: 35.8 %) and reduces REHA temperature by 2.5 °C, demonstrating its potential to advance REHA applications in space-constrained military vehicles.